A Smarter Way to Improvise Learning Outcome based on Computer Application (International Journal of Innovative Research in Computer Science & Technology, 2019)
In any educational quality improvement  endeavor, measurement plays a major role since it  provides the information for any decision making  mechanism. There is always a need to devise a  standard teaching model which can be used as a  benchmark to evaluate the quality of education  imparted. Based on the output, preventive as well as  corrective line of action can be taken, if required. The  present research deals with a standard prototype  application developed for a leading academic  institution. It has served as a basis of a simple, user friendly interface to manage the entire training cycle  with excellent results. The project has been tested at  a user level. The project has been developed in a less  known relational database called FileMaker which is  a product of Apple Company. The current project which has been named as EduGain version 1.0 which be demonstrated practically during any research assignment.
Keywords: RDBMS; ICT; Information Technology; Edugain; FileMaker